The Flying Phoenix : Aspects of Chinese Sectarianism in Taiwan - Jordan, David K.; Overmyer, Daniel L., 1935- (Book collections on Project MUSE., 2014)
Anthropologist David Jordan and Daniel Overmyer, a historian of religions, present a joint analysis of the most important group of sectarian religious societies in contemporary Taiwan: those that engage in automatic writing seances, or worship by means of the phoenix"" writing implement. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these importan